Diseño de un plan de marketing turístico para el Hotel Escuela de la Espam MFL en el cantón Bolívar- provincia de Manabí. - Moreira García, Onaira Karina (2013)
The tourism marketing plan for the Hotel School of the ESPAM was conducted at Bolívar Canton in order to solve the problem due to the lack of strategies to manage the hotel, needing real guests so students can have professional practice. The methodological procedure was divided into three phases: first phase was the situational analysis to determine the geographical area of study, then phase two the analysis of hotel school which was performed an analysis of the major areas through bibliographic research and interviews not structured, the visitor profile was determined by surveys in Zone 4 of Ecuador (Manabí and Santo Domingo), subsequently developed a matrix matching competition used to test differences between the Hotel School and the competition; and to determine a strategic analysis the SWOT matrix tool was used. Last phase is strategic marketing decisions, the elemental part which is determined objectives by the proposed mission, vision and policies, and executed strategies, which are segmentation strategies to know what type of segment is going to lead the development and differentiation strategy to set a comparison of the competition, the marketing mix strategy is also established at this stage resulting in the solution to manage the Hotel School.